2003
DOI: 10.1042/cs1040189
|View full text |Cite
|
Sign up to set email alerts
|

Levels of adhesion molecules do not decrease after 3 months of statin therapy in moderate hypercholesterolaemia

Abstract: Studies in animals and humans indicate a pivotal role for adhesion molecules (AMs) in the pathogenesis of atherosclerosis. Whereas an association between hypercholesterolaemia and AM expression has been suggested, it is unclear whether lowering cholesterol decreases AM expression and release. We compared the effects of a 3-month treatment with standard doses of three different statins (atorvastatin, simvastatin and pravastatin) on plasma levels of circulating AM (cAM) in 75 hypercholesterolaemic patients in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…The increase in ICAM‐1 concentrations (7.9%) after 24 weeks found in our study is higher, as reported by Jilma et al. [44], in patients with moderate hypercholesterolaemia. In this study, a modest increase in ICAM‐1 (2.1%), VCAM‐1 (2.7%) and E‐selectin (1.7%) was found after 3 months’ treatment with standard doses of three different statins.…”
Section: Discussionsupporting
confidence: 65%
“…The increase in ICAM‐1 concentrations (7.9%) after 24 weeks found in our study is higher, as reported by Jilma et al. [44], in patients with moderate hypercholesterolaemia. In this study, a modest increase in ICAM‐1 (2.1%), VCAM‐1 (2.7%) and E‐selectin (1.7%) was found after 3 months’ treatment with standard doses of three different statins.…”
Section: Discussionsupporting
confidence: 65%
“…Shed (soluble) adhesion molecules are well-known markers for atherosclerotic disease (36)(37)(38), and several studies indicated that statins down-regulate circulating soluble ICAM-1, vascular cell adhesion molecule 1 (39)(40)(41), and E-and P-selectin (42,43). However, not all studies that examined the effects of statins on the soluble levels of these molecules have replicated these findings (44,45).…”
Section: Statins As Antiinflammatory Drugs: Effects On Cells and Tissuesmentioning
confidence: 99%
“…Increased levels of sICAM-1 were also found in type 2 diabetic patients (Becker, van Hinsbergh et al 2002). Serum levels of sICAM-1 in cardiovascular patients treated with statins were confirmed to be lower in some groups (Romano, Mezzetti et al 2000;Blann, Gurney et al 2001;Bickel, Rupprecht et al 2002), whereas some studies could not find a significant reduction (Rauch, Osende et al 2000;Jilma, Joukhadar et al 2003).…”
Section: Sicam-1 As a Biomarker In Vascular Diseasementioning
confidence: 91%